2008
DOI: 10.1152/ajpheart.00532.2008
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome inhibition decreases cardiac remodeling after initiation of pressure overload

Abstract: We tested the possibility that proteasome inhibition may reverse preexisting cardiac hypertrophy and improve remodeling upon pressure overload. Mice were submitted to aortic banding and followed up for 3 wk. The proteasome inhibitor epoxomicin (0.5 mg/kg) or the vehicle was injected daily, starting 2 wk after banding. At the end of the third week, vehicle-treated banded animals showed significant (P<0.05) increase in proteasome activity (PA), left ventricle-to-tibial length ratio (LV/TL), myocyte cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
82
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 54 publications
7
82
0
Order By: Relevance
“…We also observed that irbesartan mainly inhibited the activity of UPS, indicating that irbesartan may exert a therapeutic effect on post-infarction ventricular remodeling, partly via the inhibition of ubiquitin expression and 20S proteasome activity. This finding was consistent with those of previous studies, which demonstrated that the inhibition of the proteasome resulted in the prevention of or decrease in pressure-induced hypertrophy in animals (6,28). UPS is an important quality control system for myocardial protein and an imbalance in this system may lead to HF (29).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We also observed that irbesartan mainly inhibited the activity of UPS, indicating that irbesartan may exert a therapeutic effect on post-infarction ventricular remodeling, partly via the inhibition of ubiquitin expression and 20S proteasome activity. This finding was consistent with those of previous studies, which demonstrated that the inhibition of the proteasome resulted in the prevention of or decrease in pressure-induced hypertrophy in animals (6,28). UPS is an important quality control system for myocardial protein and an imbalance in this system may lead to HF (29).…”
Section: Discussionsupporting
confidence: 93%
“…Detailed knowledge regarding proteasome dynamics in cardiac disease phenotypes is essential for the development of therapeutic strategies (4). Previous studies demonstrated an effective reduction of LV hypertrophy via the inhibition of proteasome function and proteasome inhibitors were used to prevent or even induce a regression of LV hypertrophy in animal models (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Protein synthesis was measured by [ 3 H]phenylalanine incorporation. 14 Apoptosis was measured by caspase-3 activity 15 and by TUNEL staining, which was performed on sections treated with 2% H 2 O 2 to inactivate peroxidases and with 20 g/mL proteinase K for permeabilization. DNA fragments were labeled with 2 nmol/L biotinconjugated dUTP and 0.1 U/L deoxynucleotidyl transferase.…”
Section: Cell Culturementioning
confidence: 99%
“…However, studies have been contradictory, showing either increased or decreased proteasomal enzyme activity in the afterload stressed LV (31, 43). Other models have demonstrated both cardioprotective (9, 21, 25, 59) and cardiotoxic (12,20,27,32,45,46) roles of the UPS via regulation of apoptosis, NF-B signaling, and oxidative stress.Although much is known about the molecular mechanisms of LVH and LV failure (LVF), the mechanisms underlying right ventricular (RV) hypertrophy (RVH) and RV failure (RVF) are less understood. RVH and RVF are a major cause of morbidity and mortality in patients with pulmonary hypertension and represent long-term risks for patients with surgically corrected congenital heart diseases such as tetralogy of Fallot, L-transposition of the great arteries, and hypoplastic left heart (4, 34).…”
mentioning
confidence: 99%
“…However, studies have been contradictory, showing either increased or decreased proteasomal enzyme activity in the afterload stressed LV (31, 43). Other models have demonstrated both cardioprotective (9, 21, 25, 59) and cardiotoxic (12,20,27,32,45,46) roles of the UPS via regulation of apoptosis, NF-B signaling, and oxidative stress.…”
mentioning
confidence: 99%